Abu Ubaid’s Perspectives And The Dynamics Of Digital Currency In Modern Islamic Economics - Mu’adzah, Nadiyah; Rachmad, Dedy; Rusydiana, Aam Slamet (LPPM ISNJ Bengkalis, 2024)
This research aims to discover how classical Muslim scholars named Abu Ubaid and contemporary academics think about the existence and Islamic law regarding digital currency. This library research uses meta-analysis, sentiment analysis, and critical analysis. This research uses secondary data from scientific journal articles published in 2017-2023. The data source in this research was obtained from the Dimension database. The research results show that there are 106 pieces of scientific literature about digital currency from an Islamic perspective and 35 scientific kinds of literature about Abu Ubaid in the economic field with fluctuating literature development. Digital currency is not based on Abu Ubaid's thinking about the function of money because digital currency is a virtual currency that does not have underlying assets and many elements of uncertainty and other harm. Contemporary research studies also indicate a prevailing inclination towards negative rather than positive sentiment regarding the presence and implementation of Islamic law in digital currency. The dar'u al-mafasid muqaddam ala jalb al-masalih principle might help resolve the dispute between those who permit and those who forbid it. This research can be used as reference material for relevant research in the future and is helpful as material for public reflection and evaluation for policymakers to revitalize the application of digital currency by Islamic principles.